Use of indigenous plant products for management of pests and diseases of spices and condiments: Indian perspective - Gahukar, R T (Journal of Spices and Aromatic Crops, 2011)
Plant derived preparations and formulated commercial products have great potential for ecofriendly management of pests and diseases of spice and condiment crops in India. These products act as antifeedant, growth regulator, repellent and a direct mortality factor against pests and as inhibitor of sporulation and development of hyphae of fungal pathogens. However, further research on field application, residual toxicity, synergistic action and hazardous effects on non-target organisms are needed.